The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/d15010029
|View full text |Cite
|
Sign up to set email alerts
|

Epibionts of an Introduced King Crab in the Barents Sea: A Second Five-Year Study

Abstract: The biodiversity, infestation patterns, and spatial distribution of organisms living in association with the introduced red king crab Paralithodes camtschaticus were studied in Dalnezelenetskaya Bay, southern Barents Sea, in 2009–20013 to update a list of species, reveal long-term changes in this epibiotic community, and identify key factors affecting the prevalence and intensity of infestation. A total of 90 associated species were found throughout the study period, or twice as many as in 2004–2008, reflectin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 77 publications
0
2
0
Order By: Relevance
“…BS and FS are two of the most productive regions in the Arctic [ 10 , 27 ], having enhanced primary production relative to other Arctic sites. The Southern BS and the Western FS support rich pelagic and benthic assemblages [ 38 , 39 , 40 , 41 , 42 , 43 ]. These systems have been intensively investigated since the 1900s [ 26 , 27 , 28 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…BS and FS are two of the most productive regions in the Arctic [ 10 , 27 ], having enhanced primary production relative to other Arctic sites. The Southern BS and the Western FS support rich pelagic and benthic assemblages [ 38 , 39 , 40 , 41 , 42 , 43 ]. These systems have been intensively investigated since the 1900s [ 26 , 27 , 28 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of studies have shown that biotic interactions occur not only between hosts and their symbionts including parasites, but also among symbionts of the same host [ 125 , 126 , 127 ]. Such interactions can play a role in shaping the community structure of co-occurring species [ 128 , 129 , 130 ]. During co-infection, helminth species can demonstrate different types of effects on each other, ranging from dramatically positive and null to dramatically negative, depending on the details of their interaction [ 131 ].…”
Section: Discussionmentioning
confidence: 99%
“…Weaker organic matter fluxes were observed at Stations 4, 5, 6, 15, and 17, where foraminiferal sand and thick layers of brown silt were found overlaying a lower layer of brown clay. In comparison, more robust sedimentation processes occurred at Stations 10,11,12,and 20. These stations exhibited a thin layer of sediment overlaying gray sediments, and a poor postmortem preservation of foraminifera was noted.…”
Section: Environmental Conditionsmentioning
confidence: 94%
“…The first, transformed Barents Sea water (BSW), is primarily composed of Atlantic water (AW) which has undergone heat loss. This water mass was detected at eight sampling stations ( Stations 4,5,6,10,11,12,15,and 20) characterized by negative water temperatures and a salinity of 34.9 psu. The second water mass, Arctic water (ArW), was observed at Station 17, with lower temperature and salinity levels compared to the BSW.…”
Section: Environmental Conditionsmentioning
confidence: 99%
See 1 more Smart Citation